Education and cyberculture: The contributions of adaptive platforms in history teaching - Carneiro, Hellen Pires (Seven Editora, 2023)
This research aims to analyze the use of adaptive platforms in the teaching of History, as well as to understand the effects of this new technological culture on the education of students. The methodology used was a literature review supported by authors who discuss: digital technologies and the teaching of History. Therefore, it is possible to observe that the insertion of this new means of communication (adaptive platforms) used as a didactic tool in the teaching of History allows for bringing the content of the student's daily life closer together, making the teaching-learning process more dynamic, capable of arresting the attention of the individual. Key points to provide quality education. DOI:https://doi.org/10.56238/devopinterscie-162